Organizational Communication Climate at DPD PAN Tanah Bumbu South Kalimantan post Change of Leader - Trisno Muldani; Bustanul Mubarok; Aminah Swarnawati (Institute of Computer Science (IOCS), 2022)
Organizations need creativity that can be created by human resources to win the competition and achieve goals. In national party organizations, creativity is not only determined by the self-factor of the regional and central administrators, but is also determined by external factors, namely the organizational communication climate. Organizational communication climate is created through interaction and communication between members of the organization. When there is a change in the organization, the atmosphere or communication climate that is created also changes. This will certainly have an impact on the smooth communication between members of the organization. This study aims to analyze the organizational communication climate in the DPD PAN, Tanah Bumbu Regency, South Kalimantan after the change of leadership. The research uses a descriptive-qualitative approach. Data collection was done by interviewing 5 informants who were taken purposively.